INISIASI TUNAS CENGKEH (Syzigium aromaticum L.) DENGAN BERBAGAI KONSENTRASI BAP SECARA IN VITRO - Haris, Abdul; Basri, Zainuddin; Bustami, Mirni Ulfa (AGROTEKBIS, 2013)
Clove tree is an annual plant that can grow to a height of 10-20 m, it has oval shaped leaves and flowering emerge in its shoots . Fruit stalk at first green, and become red if it is blooming. This study aims to determine the best concentration of BAP on shoot clove growth in in vitro. This research has been carried out in the Laboratory of Plant Biotechnology, Faculty of Agriculture, University of Tadulako, Palu, from August to September 2012. The material used was sterile shoots Cloves 1 month of age as much as 9 buds, study design using a Completely Randomized Design with 3 treatments, using 5 ppm BAP + 0.5 ppm NAA, 6 ppm BAP + 0.5 ppm NAA, 7 ppm BAP + 0.5 ppm NAA. Each treatment was repeated 3 times sothere were 9 experimental units. Data were analyzed by ANOVA followed by Duncans test. The results showed that treatment 6 ppm BAP + 0.5 ppm NAA showed a significant effect on the shoots and leaves of clove.